The Keys of Middle-earth - Lee, Stuart. author. aut Link
XV, 380 p.
Keywords: A comprehensive introduction to the medieval languages and texts that inspired Tolkien's Middle-earth. Using key episodes in The Silmarillion , The Hobbit , and The Lord of the Rings , medieval texts are presented in their original language with translations. Essential for those who wish to delve deeper into the background to Tolkien's mythology.